ГАРАНТІЇ ПРАВА КОМУНАЛЬНОЇ ВЛАСНОСТІ ПРИ РЕАЛІЗАЦІЇ ПРОЦЕДУРИ БАНКРУТСТВА СУБ’ЄКТІВ ГОСПОДАРЮВАННЯ В ЕКОНОМІЦІ МІСТА - Durneva, Yu.A. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2011)
The paper covers the issues of bankruptcy procedure as applied to the communal enterprises arid economic societies of communal and state sectors of economy. It analyses the statistical data and judicial practice in the regard of communal enterprises. Based on the results of researches, the proposals on before-court and judicial sanitation of managing subjects of the communal sector are made, as well as on realization of bankruptcy procedure for managing subjects of the communal sector of economy.